Scorpions from the north Cerrado of Tocantins: A brief report and list of animals deposited in collection (Research, Society and Development, 2023)
The Araguaína region has a phytophysiognomy predominantly with typical characteristics of a savannah with sparse trees and shrubs, herbs, and grasses. However, it is an ecotonal region between the Amazon Rainforest, Mata dos Cocais and Cerrado. Presenting high biodiversity, with species adapted to the conditions of acidic soil, prolonged dry season, and periodic fires. The heterogeneous physiognomy of the vegetation presents different strata of height and density, resulting in a mosaic of microhabitats. Being classified as Cerrado Sensu stricto, with the presence of its subtypes, in addition to the presence of herbaceous and shrubby species characteristic of each type. The region's climate is characterized by a prolonged dry season, with a rainy period occurring between November and April. The animals collected in the municipality of Araguaína and deposited in the scientific collection of the Biology Laboratory of the SESI School of Araguaína/TO, were fixed in 70% ethyl alcohol, a common technique for the conservation of organisms of the Arthropoda group. Of these, 136 animals were identified in 10 species, the most abundant being Opisthacanthus cayaporum and Jaguajir agamemnon, corresponding to 91.91% of the total number of animals. And J. agamemnon and species of the Tityus group are considered medically important scorpions, emphasizing the importance of the region for future studies of this group. Therefore, the objective of this study was to identify the scorpion species from the vicinity of the municipality of Araguaína/TO and deposited in the referred scientific collection of the biology laboratory.